2013
DOI: 10.1002/jbm.a.34861
|View full text |Cite
|
Sign up to set email alerts
|

MC3T3‐E1 and RAW264.7 cell response to hydroxyapatite and alpha‐type alumina adsorbed with bovine serum albumin

Abstract: Initial cell responses following implantation are important for inducing osteoconductivity. We investigated cell adhesion, spreading, and proliferation in response to native and bovine serum albumin (BSA)-adsorbed disc of hydroxyapatite (HA) or alpha-type alumina (α-Al2O3) using mouse MC3T3-E1 osteoblastic cells and mouse RAW264.7 macrophages. The adsorbed BSA inhibited adhesion and spreading of MC3T3-E1 cells, but did not affect MC3T3-E1 cell proliferation on HA and α-Al2O3 substrates. Thus, MC3T3-E1 cells qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…On the contrary, albumin is a major component in the human saliva and is known as cell adhesion-inhibiting protein. Kawashita et al reported that albumin adsorbed hydroxyapatite and alumina inhibited the adhesion and spreading of MC3T3-E1 cells [ 15 ]. Thus, it is important to observe protein adsorption to Ti and ZrO 2 to identify biological properties of Ti and ZrO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, albumin is a major component in the human saliva and is known as cell adhesion-inhibiting protein. Kawashita et al reported that albumin adsorbed hydroxyapatite and alumina inhibited the adhesion and spreading of MC3T3-E1 cells [ 15 ]. Thus, it is important to observe protein adsorption to Ti and ZrO 2 to identify biological properties of Ti and ZrO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, FDA staining was performed in this study for the quantitative evaluation of cell growth by fluorescent staining and visual observation of live cells grown on disk samples as described in Kawashita et al. 51 Results obtained for both V79 and MC3T3-E1 cell lines confirmed that cell growth increased over time on both TMSZ and cpTi. It was confirmed that TMSZ showed biocompatibility equivalent to that of cpTi for the growth of V79 and MC3T3-E1 cells.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, their biocompatibility, biodegradability, low immunogenicity and cost, and their ability to support cell adhesion, proliferation, and differentiation [22,23,24,25,26] mean they have significant potential in bone tissue engineering [26,27,28,29,30]. Osteoconductivity is a significant property of biomaterials which chemically bonds to bone and supports bone formation [31]. Hydroxyapatite (HAp), a major component of bone mineral, is an osteoconductive biomaterial [31,32,33] that has been generally used to make scaffolds for bone tissue engineering [34,35,36,37,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoconductivity is a significant property of biomaterials which chemically bonds to bone and supports bone formation [31]. Hydroxyapatite (HAp), a major component of bone mineral, is an osteoconductive biomaterial [31,32,33] that has been generally used to make scaffolds for bone tissue engineering [34,35,36,37,38,39]. Previously, a chitosan/alginate/SiO 2 (CS/Alg/SiO 2 ) composite scaffold prepared by freeze-drying was demonstrated to have a 3D microporous structure, controllable biodegradation, and improved apatite deposition performance that enhanced bone tissue repair [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation